SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN PAKAN TERBAIK PEMBESARAN IKAN LELE SANGKURIANG HEMAT BIAYA MENGGUNAKAN METODE TOPSIS - Jhons Fransdesker; Sri Primaini; Nazori Suhandi (UNIVERSITAS INDO GLOBAL MANDIRI)
Decision support systems (decision support systems) is a computer-based information system including a knowledge-based system or the management of knowledge that is used to support decision making in an organization or individual. Sangkuriang catfish (Clarias gariepinus) is one freshwater fish species are cultivated commercially by the people of Indonesia. Feed apart as one of the factors that can increase the productivity of fish, also the largest component in the production cost. Can reach 60% of the total cost of production. Currently the price of manufactured feed expensive per kgnya. For the best quality feed and has a cost efficient is certainly not easy. It is necessary for a merger of several disciplines to obtain optimal feed value. In the field of informatics, experiences to look for the best optimal feed (have good nutritional value, but the price is efficient). The method used is TOPSIS (Technique for Order Preference by Similarity to Ideal Solution). This uses the principle that the selected alternative should have the shortest distance of a positive solution and farthest from the negative ideal solution of a geometrical point by using the Euclidean distance to determine the relative proximity of an alternative to the optimal solution. This study discusses the assessment, analysis and development of a decision support system determine the best feed catfish enlargement sangkuriang cost-effective.